2021
DOI: 10.3389/fpsyt.2021.664517
|View full text |Cite
|
Sign up to set email alerts
|

“We Thought We Were Alone”: The Subjective Experience of the Siblings of Anorexic Adolescent Patients

Abstract: Objective: The siblings of patients suffering from Anorexia Nervosa (AN) are potentially affected by a disturbed emotional experience that often remains undetected. In order to bring them a psychological support, the Maison de Solenn proposed a support group program for these siblings. The current research explores their mental representations of AN and their emotional experience in the support group named “sibling group.”Method: This exploratory study is based on a phenomenological and inductive qualitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Communication between siblings and their SED becomes more limited and restricted (Areemit et al., 2010). Siblings become cautious about what topics can be spoken about (Persico et al., 2021) in order to reduce conflict (Karlstad et al., 2021) as some topics become off limits (Grunwald, 2014). Siblings may be more sensitive to language related to body shape and size and feel angry when people use words like “fat” and “diet” (Areemit et al., 2010, p. 571).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Communication between siblings and their SED becomes more limited and restricted (Areemit et al., 2010). Siblings become cautious about what topics can be spoken about (Persico et al., 2021) in order to reduce conflict (Karlstad et al., 2021) as some topics become off limits (Grunwald, 2014). Siblings may be more sensitive to language related to body shape and size and feel angry when people use words like “fat” and “diet” (Areemit et al., 2010, p. 571).…”
Section: Resultsmentioning
confidence: 99%
“…Siblings struggled to voice their experiences and communicate their feelings (Moses, 2013; Persico et al., 2021). Siblings fear sharing their experiences with others as it is often perceived negatively by the family unit, including their SED (Moses, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third study [32] reported how healthy sisters (n = 21) of women with ED may also evince more difficulties and avoidance in the recognition of their own emotions as compared to non-related controls, through both self-report and experimental task based on picture of faces. Further recent studies proposed additional qualitative reports of distress in this population [33,34].…”
Section: Psychological Mechanismsmentioning
confidence: 87%
“…Finally, research into the efficacy of preventative interventions for siblings of people with AN would be valuable. Some evidence suggests that a support group for siblings of people with AN may be helpful but is it unclear whether this is protective against the development of eating disorder pathology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%